Block Chain : Opportunities for Private Enterprises in Emerging Market - Niforos, Marina (International Finance Corporation, Washington, D.C., 2017)
The six chapters that follow provide an overview of the technology (chapter one) and its unfolding applications in emerging markets (chapter two). Chapter three examines whether blockchain can be used to mitigate de-risking by financial institutions. Chapters four and five look more closely at the financial services sector, including an overview of how blockchain affects plays into the wider spectrum of financial technology (fintech) innovations and the resulting provision of financial services (chapter four), and an analysis of blockchain’s contribution to reaching the unbanked and underbanked in various emerging markets, including in Latin America, Asia and countries in Sub-Saharan Africa (chapter five). Finally, Chapter six looks ‘beyond fintech’ and explores how developments in applied blockchain technology can impact agribusiness, drug safety and more generally provide enforcement tools to promote the reach of sustainable and inclusive business. These chapters are merely the beginning of an exploration. Sound use cases for blockchain beyond cryptocurrencies are yet to be validated. As money pours into the latest novel technology, it is important to distinguish hype from reality, and to avoid assuming validation due to investments made under the ‘fear of missing out,’ a popular Silicon Valley investment decision heuristic. The enduring value of blockchain’s accelerated investment cycle may be that it has fostered intense experimentation and focused attention on the fundamental nature of ledgers, transactions, counterparty connectivity, and the role of trust.